Association of TGF-β1 and IL-10 gene polymorphisms with osteoporosis in a study of taiwanese osteoporotic patients - Tu, Min-Yu; Han, Kuei-Yang; Lan, Ying-Wei; Chang, Ku-Yi; Lai, Cheng-Wei; Staniczek, Theresa; Lai, Chung-Yu; Chong, Kowit-Yu; Chen, Chuan-Mu (Genes, 2021)
Osteoporosis is a rising health threat in the increasingly aging world population. It is a common skeletal disease strongly linked to genetic predisposition. We aim to identify the effects of the anti-inflammatory TGF-β1- and IL-10-specific single-nucleotide polymorphism (SNP) combination on the risk for osteoporosis. We investigated and analyzed the relationships between three TGF-β1 SNPs (−509C/T, +869 T/C and +29T/C), one IL-10 SNP (+1927A/C) and the level of bone mineral density (BMD), as well as the risk of osteoporosis in Taiwanese osteoporotic patients. A total of 217 subjects were recruited, including 88 osteoporotic patients and 129 healthy controls, for SNPs, BMD and clinical characteristics statistical analyses. Females with TGF-β1 SNP (−509 C/C) and IL-10 SNP (+1927 C/C) genotypes showed a great benefit for femoral neck T-scores. However, the combination of TGF-β1 SNP (−509 T/T) and IL-10 SNP (+1927 A/A) genotypes in all subjects showed a significant decrease in total hip BMD T-scores. The TGF-β1 SNP (−509 C/T) genotype in all subjects and TGF-β1 SNP (−509 T/T) and IL-10 SNP (+1927 A/C) genotypes in males showed positive effects on body height. The combination of the many SNPs in the anti-inflammatory TGF-β1 and IL-10 genes may be cooperatively involved in the development of osteoporosis. Our data suggested that the specific SNP combination of TGF-β1 (−509) and IL-10 (+1927) may act as a predictive factor for postmenopausal osteoporosis in Taiwanese women.
Gesehen am 18.10.2021